The construction of masculinities: male university students' talk about women and heterosexual relationships - Minnaar, Benita (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
This article examines the talk of male Psychology students about women and heterosexual relationships in all-male discussion groups. Four vignettes depicting difficult situations in heterosexual relationships were used to initiate discussion. Eight men attending a historically black university participated in the group discussions, which were facilitated by a male postgraduate Psychology student. The study explored masculine identity construction by identifying interpretive repertoires deployed by respondents to construct and account for themselves and their social worlds, within the context of discussions about relationships with women. Three interpretive repertoires of masculinity: the male-as- breadwinner/provider, male-as-protector and the "New Man" repertoire were identified. The complex and contradictory nature of masculine identity construction is highlighted. Drawing on the work of Hollway (1984), two discourses of heterosexuality were also identified: the have/hold discourse and the permissive discourse. The invocation of the "New Man" repertoire and pro-feminist discourses of heterosexuality in the men's talk may signify a move towards more enlightened and less oppressive constructions of masculinity, heterosexuality and gender.
Keywords: Masculinity; Men -- Identity; Men -- South Africa; Men -- Conduct of life; Discourse analysis; Heterosexuality -- South Africa